Il delicato bilanciamento costituzionale fra libertà di parola e tutela del sentimento religioso: profili comparati (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Premessa - 2. Il quadro costituzionale in Pakistan - 3. La tutela del sentimento religioso nel codice penale pakistano - 4. Il quadro costituzionale tedesco - 5. La tutela del sentimento religioso nel codice penale tedesco - 6. Conclusioni.The delicate constitutional Balance between Freedom of Speech and the Protection of religious Sentiment: comparative ProfilesABSTRACT: The article focuses on the issue of freedom of speech and freedom of religion from the point of view of two countries with specific legislation in place (Pakistan and Germany). In particular, we will examine the two Constitutions and the two Criminal Law, which proved to have very different ways of expressing their sensitivity and a great attention to the religious sentiment of the population.